Saneamento básico no Brasil: avaliação dos fatores determinantes do investimento com base nos dados da pesquisa do Sistema Nacional de Informações sobre Saneamento (SNIS) - Santos, Fernando Oliveira (2016)
This study aims to identify and analyze the importance of determining factors for investment in sanitation in Brazil in 2014. As a source of information it was adopted the National Sanitation Information System survey data base. The sustainable development goals of the United Nations Organization, as well as the Brazilian Sanitation Act (Act nº 11,445, January 5th, 2007) and the national plan for basic sanitation (Plansab) focus on universalization of attendance/deficit reduction. In 2007 were implemented important public policies: i) the Sanitation Act, wich filled the legal framework gap reducing the legal uncertainty of the sector, and ii) the Growth Acceleration Program (Programa de Aceleração do Cresimento – PAC), that virtually eliminated the problem of scarcity in the supply of financial resources, with significant impact on the change of level of investments in the sector, doubling it. Considering this context it is questioned what other factors could impact investment in the sector? The results of the study show that the size of the service provider is configured as the main element to explain the volume of investments. The deficit sets up as a second factor but with much lower power than the first. This study explains and identifies the determining factors that really can impact the flow of investments in the sector and the misalignments between the desired goals/plans drawn up focusing on deficit reduction compared to investment effectively performed.